To end in fire - Weber, David, 1952-; Flint, Eric (Weber, David, 1952-. Crown of slaves, 2022)
Solarians will never accept the "war guilt" of the League, because they know the Grand Alliance was just as bad. And in the fullness of time, Solarians will seek vengeance upon their enemies. Not all Solarians feel that way, but even some of those who accept that there was an interstellar conspiracy cherish doubts about its origins. But it is still out there, and now defeated Solarians and agents of the victorious Alliance must join forces to find it. Even if they don't believe in it, it believes in them.